2008
DOI: 10.1063/1.2983632
|View full text |Cite
|
Sign up to set email alerts
|

Pinned emission from ultrasmall cadmium selenide nanocrystals

Abstract: We report pinning of the emission spectrum in ultrasmall CdSe nanocrystals with a diameter of 1.7 nm and smaller. It was observed that the first emission feature ceased to blueshift once the band edge absorption reached 420 nm, though the band edge absorption continued to blueshift with decreasing nanocrystal diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(86 citation statements)
references
References 21 publications
3
83
0
Order By: Relevance
“…Ultrasmall CdSe nanocrystals synthesized with a surfactant mixture of dodecylphosphonic acid, hexadecylamine and tri-n-octylphosphine oxide have an additional emission feature residing between a strongly Stoke-shifted first emission peak (not believed to be band-edge) and the broad deep trap emission 35, 40,41 Figure 1. shows a typical absorption and emission spectrum of ultrasmall CdSe, which produces a balanced white-light emission with Commission internationale de l'éclairage (C.I.E.)…”
Section: Ultrasmall White Light-emitting Cdse Nanocrystalsmentioning
confidence: 99%
“…Ultrasmall CdSe nanocrystals synthesized with a surfactant mixture of dodecylphosphonic acid, hexadecylamine and tri-n-octylphosphine oxide have an additional emission feature residing between a strongly Stoke-shifted first emission peak (not believed to be band-edge) and the broad deep trap emission 35, 40,41 Figure 1. shows a typical absorption and emission spectrum of ultrasmall CdSe, which produces a balanced white-light emission with Commission internationale de l'éclairage (C.I.E.)…”
Section: Ultrasmall White Light-emitting Cdse Nanocrystalsmentioning
confidence: 99%
“…Similarly, Puzder et al suggested that surface states are responsible for the pinning of the conduction band [21]. Recently, Dukes et al concluded that the pinned emission is due to a surface state introduced by a phosphoric acid ligand bound to the nanocrystal surface [18]. By contrast, Zanella et al merely associated the fixed peaks in the absorption spectra with the discontinuous growth of groups II-VI semiconductor nanocrystals [22].…”
Section: Introductionmentioning
confidence: 95%
“…Decrease in nanocrystal diameter results in the blueshifting of the band-edge emission and band-edge absorption through the quantum confinement effects [14][15][16][17][18]. However, optical band gap insensitivity occurs when the particle sizes are less than 2 nm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations